Antidiabetic Effect of Urena lobata: Preliminary Study on Hexane, Ethanolic, and Aqueous Leaf Extracts - Wahyuningsih, Doti; Purnomo, Yudi (Jurnal Kedokteran Brawijaya, 2018)
Chronic hyperglycemia is one of the signs of human type-2 diabetes mellitus due to insulin resistance and depletion. This study aimed to evaluate hexane, ethanolic, and aqueous leaf extracts of Urena lobata as antihyperglycemic agent. Design of this study was a post-test only control group using 25 male Sprague-Dawley rats divided into 5 groups. High fructose diet (HFD) ad libitum and single dose of intraperitoneal streptozocin (STZ) (25 mg/kgBW) were administered to induce diabetes in rats. Three groups of the diabetic rats orally received 500 mg/kgBW of only a type of leaf extract of U. lobata for 4 weeks. Insulin serum levels were measured using enzyme-linked immunosorbent assay (ELISA) method. Size, shape, and density of the islet cells were observed by light microscope. Blood glucose level and the area under curve (AUC) of serial oral glucose tolerance test (OGTT) were measured. The U. lobata leaf extracts of three types of solvent all increased serum insulin level and improved Î² cells condition, also decreased the AUC of the OGTT series in diabetic rats. Values were compared with untreated diabetic rats (p<0,05). The aqueous leaf extract of U. lobata was the best in increasing insulin serum level, recovering islet cells condition, and correcting blood glucose level. The hexane extract showed poor results when compared to the other soluble agents.